Dyslexia - Glazzard, Jonathan; Stones, Samuel; Glazzard, Jonathan; Stones, Samuel (IntechOpen, 2021)
This book includes a variety of perspectives on dyslexia from different contexts. Chapters provide examples of empirical research; the outcomes of which have the potential to improve the experiences of individuals with dyslexia. The book emphasises the importance of adopting a capability rather than a deficit approach.
English
Keywords: Learning